DYNAMICS OF SOCIAL TIES IN URBAN SPACE AND THEIR MANIFESTATIONS IN EVERYDAY LIFE INTERACTIONS: AN ETHNOGRAPHIC STUDY IN EL-WIAM NEIGHBORHOOD – LAGHOUAT - Zobiri Khayra Nour, (International Journal of Innovative Technologies in Social Science, 2025)
This article examines how social ties are formed within new urban spaces in Algeria, through an ethnographic field study conducted in the El-Wiam neighborhood of Laghouat city. The importance of this research stems from the transformation of neighborly relations and social interactions in the context of rapid urbanization and population diversity, which raises questions about the nature of relationships within the modern urban neighborhood.The study aims to understand how everyday social relations are constructed and reshaped within the neighborhood, and what factors influence them. A qualitative ethnographic approach was adopted, using participant observation and in-depth interviews with a purposive sample of 32 participants from diverse age and cultural backgrounds.The findings revealed that neighborly relations are characterized by reservation and superficiality, and are shaped more by geographic and symbolic belonging than by physical proximity. Digital media play an increasing role in reproducing unstable relationships, and public and private spaces are used in unbalanced ways depending on gender and generation. The study concludes that social ties in the urban neighborhood are socially produced and remain fragile amid socio-spatial and digital transformations.